STUDI KELAYAKAN FINANSIAL WISATA ALAM SERIBU BATU SONGGO LANGIT BANTUL - ENGGAR TYASTUTY; RIFKI KHOIRUDIN; DINI YUNIARTI (LP2MTBM MAKARIOZ, 2021)
Seribu Batu Songgo Langit is a tourist destination that boasts the beauty potential of pine, a vehicle based on knowledge,culture, and to keep up with the times without destroying the main function of the forest. The purpose of this research is todetermine the cost and benefits that have been obtained by analyzing the financial feasibility of the Seribu Batu SonggoLangit in Bantul. This study uses quantitative methods with analysis tools of Net Present Value (NPV), Internal Rate ofReturn (IRR), and Benefit Cost Ratio (B/C Ratio). From the calculation process that has been carried out, the NPV result are–Rp 754,80 million rupiah, an IRR of -5,42%, and B/C Ratio of 1,04. So, it can be conclude that the Environmental Servicesof Seribu Batu Songgo Langit Nature Tourism are not financially feasible, but in terms of the benefits and costs, it generatesa benefit of 1,04 when run.